ANALYSIS OF HEMOGLOBIN VARIANTS USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY IN BETA THALASSEMIA (HPLC) - Saba Iqbal; Faiqua Yasser; Alveena Nawaz; Komal Naveed; Bisma Ahmad; Mahwash khan (International Journal of Contemporary Issues in Social Sciences, 2023)
The most prevalent genetic blood disorder in the world, beta-thalassemia is typified by base negotiation, or the minor omission or insertion of one or two nucleotides in the globin gene. These days, because of the mixing of the gene pool, this issue is not limited to any one ethical group of races; rather, each group reflects a unique set of mutations. A quick, sensitive, and accurate method for identifying aberrant hemoglobin fragments is High-Performance Liquid Chromatography (HPLC). A total of 55 cases of beta-thalassemia from Lahore and surrounding areas have been examined for vibrant hemoglobin variations. This is an observational (Prospective and Retrospective) study carried out in the Department of Pathology in CMH LMC & IoD. The study was performed on Agilent 1220 perpetuity LC (Agilent Technologies) a High-Performance Liquid Chromatography (HPLC) using EZChrom Elite for Beta-thalassemia. Abnormal hemoglobin variants were anatomized for 55 cases of Beta-thalassemia on High-Performance Liquid Chromatography (HPLC). There were about 18 cases of beta-thalassemia major and 37 cases of beta-thalassemia carriers. The frequency observed in our study was HbA1c (0.51), HbF (0.18), HbE (0.13), HbD (0.86), HbS (0.17), and HbA2(0.15). Automated High-Performance Liquid Chromatography is an applicable approach for the webbing and plausible identification of cases as well as carriers of Beta-thalassemia previous to DNA studies for a definitive opinion.